Strengthening the Quality of Hadith Studies at PTKIN through the Contribution of PKH: A Case Study of ‘Gebyar Hadis’ at UIN Sultan Maulana Hasanuddin Banten - Karina, Ayu; Rio Kurniawan; Azis Arifin (The Future of Education Journal, 2025)
This study aims to analyze the innovative contributions of the Central Hadith Study Institution (PKH) in strengthening the quality of Hadith studies within the context of State Islamic Higher Education Institutions (PTKIN). The research employed a qualitative method using a descriptive-analytical library research approach. Data were collected through a systematic review of relevant literature and documents related to Hadith studies in PTKIN. The findings indicate that PKH plays a significant role in developing the ecosystem of Hadith studies in PTKIN through methodological innovations in Hadith scholarship.